"Uscire dalla vita" — Il Secretum come biografia non-vera di Petrarca - Tombi, Beáta (Verbum – Analecta Neolatina, 2005)
In my paper, I am going to study Petrarch’s autobiography through a standard theory of postmodern deconstructionism, and confute the traditional concept of this genre. According to this proposal, every text, canonized by tradition, breaks away from its own place, in order to reorganize everyday tabulations. My work proceeds at two levels. The first part is framed by the traditional quality of the act of writing/reading as self-confession or self-examination. The exact study of Secretum results in a new theory: the autobiography essentially becomes a kind of writing or reading method, recurring in every kind of text. The second part is dedicated to the true or verifiable character of the same composition. Shortly, in this part, I am going to confirm my previous hypothesis through the application of several philosophical prospects. Actually, this critical attitude results in the review of traditional paradigms turning every autobiography into a false-autobiography and all kinds of text into a virtual autobiography.